Penerapan Metode Promethee pada Perekrutan Calon Pegawai Non PNS Bawaslu Kabupaten Simalungun - Rodiah, Siti; Damanik, Irfan Sudahri; Suhendro, Dedi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The importance of the quality of the workforce that will be used makes management work hard and be careful in determining the criteria that will be determined for the decision making process for the recruitment of prospective workers. The authority to recruit non-civil servant election supervisors is also the full authority of Bawaslu in the process must be maximized. At present, the process of recruiting non-PNS Bawaslu employees in Simalungun Regency has not been systemized and computerized which results in suboptimal recruitment results because many employees recruited are still in doubt of their credibility. PROMETHEE is one of the Multi Criteria Decision Making (MCDM) methods, which means determining or sorting in a multi-criteria analysis, this method is known for its efficient and simple concept, in addition to solving problems related to multi criteria, this method is also very easy to applied rather than other methods. In this study, the PROMETHEE II method is used to obtain qualified employee recruitment in accordance with the desired criteria and the results of existing grades